Estes Valley Fire Protection District - State Fire Assistance - Colorado State Forest Service, compiler (Colorado State University. Libraries, 2009)
Located in: Fort Collins office files. Estes Valley Fire Protection District (EVFPD) records related Colorado State Forest Service (CSFS) State Fire Assistance (SFA) program. Includes: program payment and reimbursement requests; disbursement voucher; cost documentation worksheets; invoices; timecards; Wildland Urban Interface (WUI) competitive grant application and summary report; EVFPD press releases concerning free residential slash collection days; and correspondence.
Keywords: Colorado State Forest Service -- History -- Sources; Forests and forestry--Colorado